Human Rights and Elections - United Nations for Human Rights Office of the High Commissioner (United Nations, 2021)
With hundreds of references to the jurisprudence of United Nations human rights mechanisms, this handbook provides human rights and electoral practitioners with a clear picture of the close interplay between elections and international human rights law. The handbook discusses international human rights standards regarding electoral processes and political participation, and how these standards apply to specific aspects of elections. Current issues such as gender-based violence in politics, disinformation and data manipulation, and the impact of Internet shutdowns are considered in the light of international human rights law and the recommendations of United Nations experts.